The Effect of SrVER Learning Model-Assisted Augmented Reality to Improve Students Learning Outcomes in Science Topic - Elynati, Muslimah; Handayani, Baiq Sri; Lestari, Tri Ayu; Jamaluddin, Jamaluddin (Jurnal Pijar Mipa, 2025)
Science learning plays an important role in developing students' thinking skills and awareness of the environment. One effort to improve the quality of science learning is by implementing innovative and engaging learning models. This study aims to determine the effect of the SrVER learning model assisted by augmented reality (AR) media on students' science learning outcomes. The SrVER learning model is a learning approach that emphasizes students' visual learning styles. This study employs a quantitative quasi-experimental method with a non-equivalent control group design. The population consists of all eighth-grade students at SMP Negeri 2 Mataram, with a sample of 160 students from four classes. The sampling technique used was purposive sampling. Data were analyzed using ANCOVA after meeting prerequisite tests such as normality and homogeneity. The study shows a difference in the experimental class's average pretest and posttest scores, with an average pretest score of 35.5 and a posttest score of 66.775. The ANCOVA test results obtained a significance value of 0.000 < 0.05, indicating that Ho is rejected and Ha is accepted. This means the SrVER learning model assisted by augmented reality (AR) significantly affects students' science learning outcomes.